Machine Learning/Deep Learning in Medical Image Processing - Nishio, Mizuho (MDPI - Multidisciplinary Digital Publishing Institute, 2021)
Many recent studies on medical image processing have involved the use of machine learning (ML) and deep learning (DL). This special issue, "Machine Learning/Deep Learning in Medical Image Processing", has been launched to provide an opportunity for researchers in the area of medical image processing to highlight recent developments made in their fields with ML/DL. Seven excellent papers that cover a wide variety of medical/clinical aspects are selected in this special issue.